Observations on the pioneer white butterfly, Belenois aurota (Lepidoptera: Pieridae) in Ker (Capparis decidua) plant in Arid region of India (Indian Journal of Arid Horticulture, 2017)
The pioneer white butterfly, Belenois aurota Fabricius, 1793 (Lepidoptera: Pieridae ), has found to be emerging as amajor pest of ker (Capparis decidua) plant in arid region of India and causes over 70% damage to wild and cultivated kerplants. During the survey of pest incidence, the maximum incidence (86.67%) was observed in first fortnight of Decemberand it was reduced to 11.67% in first fortnight of September in subsequent year. The average numbers of insects rangedbetween 1.33 to 10.33 larvae per branch of plant. Adults of this small butterfly were blacks and whites in color with blackmarkings on both upper and under sides broader, the white spots on black apical area of fore wing often sub-obsolete above.Eggs were laid in batches on young shoots or new branches and were 1.74 mm in length, 1.55 mm in width and yellow incolor when first laid. The length and width of 1st instar larvae were 2.05 mm and 0.47 mm, respectively and feed on branchesgregariously. There were total of five instars. Pupae were 18.84 mm long and 4.92 mm wide. Adult females had a bodylength of 13.23 mm and a wingspan of 41.65 mm. Bodies of males were 11.54 mm long and their wingspan measured 38.72mm.
Keywords: Belenois aurota; Capparis deciduas; incidence; morphological characterization